2013
DOI: 10.1167/iovs.12-10865
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Biomarker Identification in Uveitis Associated With Juvenile Idiopathic Arthritis

Abstract: PURPOSE.To investigate the presence of biomarkers in aqueous humor (AH) from patients with uveitis associated with juvenile idiopathic arthritis (JIA).METHODS. AH (n ¼ 73) and serum (n ¼ 105) samples from 116 children were analyzed using surface enhanced laser desorption/ionization time of flight mass spectrometry (SELDI-ToF MS). The samples were divided into the following groups: JIA, silent chronic anterior uveitis (AU), other uveitis entities, and noninflammatory controls. Statistical biomarker identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…96 In the JIA group, a protein later identified as trans thyretin was expressed at a significantly higher level than in individuals with other forms of uveitis and controls. The exact role of transthyretin in JIA-associated uveitis, and whether it is involved in the pathogenesis of this disorder, is unclear.…”
Section: Reviewsmentioning
confidence: 93%
See 1 more Smart Citation
“…96 In the JIA group, a protein later identified as trans thyretin was expressed at a significantly higher level than in individuals with other forms of uveitis and controls. The exact role of transthyretin in JIA-associated uveitis, and whether it is involved in the pathogenesis of this disorder, is unclear.…”
Section: Reviewsmentioning
confidence: 93%
“…96 Researchers obtained aqueous humour samples from 17 patients with JIAassociated uveitis, 39 with other forms of uveitis and 20 113,114 Abbreviations: CTLA-4, cytotoxic T-lymphocyte-associated antigen 4; mAb, monoclonal antibody; RCT, randomized controlled trial.…”
Section: Systemic Dmardsmentioning
confidence: 99%
“…41 Similarly, it has been also reported higher levels of transthyretin are present in the aqueous of patients with JIA-associated uveitis and silent chronic anterior uveitis compared to those of the other uveitis types and control groups. 42 Recently, a study has shown an association between parvovirus B19 and JIAassociated uveitis. In this study an intraocular antibody production against parvovirus B19 was found by Goldmann-Witmer coefficient in 7 of 13 patients with JIA-associated uveitis and only 3 of 45 patients with anterior uveitis of undetermined origin.…”
Section: G Undifferentiated Arthritismentioning
confidence: 99%
“…Two of the 11 patients with uveitis, elevated urinary β2M, and no other signs of AIN were diagnosed as having another clinical entity including herpes simplex virus infection (confirmed by an aqueous humor analysis) and ANA-positive chronic anterior uveitis with no signs of arthritis. 12,13 The conditions of the other 9 patients remained undiagnosed despite comprehensive additional testing. Next, we calculated the predictive value of the specific tests with respect to detecting definitive and/or probable TINU syndrome.…”
Section: Additional Characteristics Of Our Study Populationmentioning
confidence: 99%